2014
DOI: 10.5114/hpr.2014.46235
|View full text |Cite
|
Sign up to set email alerts
|

Familial risk of dyslexia in Polish first grade pupils based on the ARHQ-PL Questionnaire

Abstract: health psychology report • volume (4), 4 original article background From the perspective of dyslexia, familial risk is the issue most researched worldwide. The familial risk has never been studied in Poland. Results of many studies conducted in Europe, the U.S. and Australia show that children who have a close family member with dyslexia are at greater risk of this disorder than children in the control groups. This conclusion is backed up by the results of research on the genetic aetiology of learning dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
8
0
3
Order By: Relevance
“…With results from correlational analyses, they concluded that ARHQ scores served as a good indicator of an adult’s past and current reading ability. The ARHQ has been adapted to multiple languages, such as Icelandic (e.g., Bjornsdottir et al, 2014), Portuguese (e.g., Alves & Castro, 2005) and Polish (e.g., Krasowicz-Kupis et al, 2014). There are also several revised versions of the ARHQ (i.e., ARHQ-R), which are also translated into languages other than English (e.g., French, see Fichten et al, 2014).…”
mentioning
confidence: 99%
“…With results from correlational analyses, they concluded that ARHQ scores served as a good indicator of an adult’s past and current reading ability. The ARHQ has been adapted to multiple languages, such as Icelandic (e.g., Bjornsdottir et al, 2014), Portuguese (e.g., Alves & Castro, 2005) and Polish (e.g., Krasowicz-Kupis et al, 2014). There are also several revised versions of the ARHQ (i.e., ARHQ-R), which are also translated into languages other than English (e.g., French, see Fichten et al, 2014).…”
mentioning
confidence: 99%
“…We used the questionnaire measure due to the fact that in Poland, reading impairment was not diagnosed when the parents of our participants were school aged. However, according to the norming study of the Polish version of ARHQ, the criterion of scoring more than 0.4 points is fulfilled by 11% of mothers and 16% of fathers (Krasowicz-Kupis et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…We concentrated on the link between NL phonological processing skills and the fluency and accuracy of decoding and word recognition skills in EFL, as these are the core symptoms in dyslexia (Lyon, Shaywitz, & Shaywitz, 2003), and, according to the LCDH, deficits in the phonological code cause difficulties in FL learning (Sparks et al, 2009; Sparks et al, 2006). Word decoding and recognition depend on phonological processing skills: phonological awareness, rapid automatised naming (RAN), and verbal short-term memory (Krasowicz-Kupis, 2008; Wagner & Torgesen, 1987). Thus, we decided to examine this set of aforementioned variables, which are regarded as core in the development of and proficiency in NL and FL reading to investigate if and how they also contribute to FL reading of Polish students learning EFL.…”
Section: Introductionmentioning
confidence: 99%